When the English fall : a novel - Williams, David (David Gerald), 1969- (Algonquin Books of Chapel Hill, 2017)
Seen through the diary of Jacob, an Amish farmer trying to protect his family and his way of life, the book examines the idea of peace in the face of deadly chaos when an Amish community in Pennsylvania is caught up in the devastating aftermath of a catastrophic solar storm and the subsequent collapse of modern civilization.